The Registration of Waqf Land in Realizing Legal Certainty in Indonesia - Damianus Krismantoro; Maria Hutapea; Tiany Swastika Pramesti Kristiyadi (West Science Law and Human Rights, 2026)
Waqf is one of the acts of worship of Muslims. Law Number 41 of 2004 stipulates that waqf is a legal act by a waqif to separate and/or transfer part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or public welfare in accordance with sharia. The waqf of land ownership in Indonesia requires professional management so that it can become a religious institution as well as an institution that can help the economy of Muslims. Waqf requires legal certainty to avoid conflicts in the future. Legal certainty is obtained by registering the waqf at the Land Office so that a certificate is obtained which serves as proof of ownership of the waqf land. The method used in this study is the normative juridical method. The data sources are secondary data. The data collection method was conducted through a literature study. Data processing was carried out using descriptive analysis. The registration of Waqf Land in the National Land Law System is carried out through the Land Registration mechanism regulated in Government Regulation Number 24 of 1997 in conjunction with Government Regulation Number 18 of 2021.